“We also have valid ideas” (Journal of Parents and Teachers, 1997)
Initiatives are proposed to encourage recycling and reduce the use of plastics, as well as the creation of natural spaces. Governments are urged to facilitate recycling and involve young people in environmental projects. International collaboration is key to environmental conservation.
Keywords: recycling; plastics reduction; environmental projects; collaboration